ANALISIS KEBERLANJUTAN EKOWISATA PANTAI SOLOP KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR - R. Sandra Agustin; Thamrin Thamrin; Sukendi Sukendi (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2021)
In the Solop Coast area, there are a variety of rare flora and fauna typical of mangrove forests which are a natural attraction for a number of tourists. The purpose of this study is to identify the ecological, economic, social and community conditions of the institution, identify and analyze the index and the status of sustainability and management of the Solop Beach mangrove forest ecotourism. This research was conducted in the Solop Beach mangrove ecotourism area in April-June 2020. The research approach to sustainable mangrove ecotourism management research is a quantitative and qualitative approach using survey methods, literature studies and interviews. The results of this study are the condition of mangrove ecotourism is seen from the types of mangroves found on Solop Beach, among others, Rhizophora apiculata, R. mucronata, Bruguiera gymnorrhiza, B. Parviflora, Xylocarpus granatum, Nypa fruticans, Acrostichum aureum. Based on the results of the Tourism Suitability Index assessment, observation station I gets an TSI value of 68%, station II gets a value of 76%, station III gets a value of 72%. TSI value at all observation stations is included in the S2 category or suitable to be used as a mangrove ecotourism object. Sustainability index and status known from the results of multidimensional analysis (MDS) shows that the sustainability status of mangrove ecosystem management in Solop Beach is 51.8 with a quite sustainable category.